Cultivo do neon goby elacatinus fígaro (sazima, moura & rosa, 1997), submetido a diferentes tratamentos alimentares - Facundo, Gabriel de Mesquita (2022)
Several species are impacted by human action through exploitation, to supply the ornamental fish market. Due to these factors, many of them may be overexploited, reaching the limit of sustainability for the activity. In this sense, the aquaculture of marine ornamental fish is the main alternative to reduce the impacts on reef species that are commonly used by aquarists. The cultivation of live food and the development of cultivation protocols makes the activity extremely viable and necessary. Thus, this work aimed to develop a breeding protocol for the neon goby (E. figaro), an endemic Brazilian species, as well as to describe the reproductive behavior and larval development of the species and to evaluate the effects of different rotifer and brine shrimp densities. On larval survival and growth. During rotifer density experiments, there were no significant differences in the survival or growth of E. figaro larvae between density treatments that were fed with 10, 15 or 25 rotifers ml−1 . However, the highest median survival was achieved when they were fed 20 ml−1 rotifers. The treatments using brine shrimp occurred from day 14 and lasted until day 35 after hatching, the control treatments were fed only with 20 rotifers/ml. During experiments with brine shrimp, survival of E. figaro larvae gradually decreased with increasing density of brine shrimp. It is noteworthy that for the species, the highest survival occurred in control treatments in which the larvae were fed only rotifers, suggesting that brine shrimp were an unsuitable prey for E. figaro larvae at this stage of development. In conclusion, other forms of food can be evaluated as well as the development of new techniques and protocols for live food cultivation and, consequently, a better development of marine ornamental aquaculture. One of the alternatives to be sought is to seek the feasibility of growing new food sources that will meet the nutritional needs of the cultivated species.